Efficiency improvement of AlGaN-based deep-ultraviolet light-emitting diodes and their virus inactivation application. (9th August 2021) - Saito, Yoshiki; Wada, Satoshi; Nagata, Kengo; Makino, Hiroaki; Boyama, Shinya; Miwa, Hiroshi; Matsui, Shinichi; Kataoka, Keita; Narita, Tetsuo; Horibuchi, Kayo
Abstract: AlGaN-based ultraviolet light-emitting diodes (UV-LEDs) are key components for the inactivation of viruses. Highly efficient and high-power UV-LEDs, capable of inactivating viruses in a short time, are in demand. For this purpose, the growth technologies of n-type AlGaN contact layers were developed from two points of view: first, to decrease the resistivity of n-type Al0.62 Ga0.38 N by minimizing the electron compensation, resulting in electronic degeneracy with metallic conduction; second, to improve the light emission uniformity in AlGaN multiquantum wells (MQWs) by controlling the morphology of the underlying n-type AlGaN layer to inhibit macrostep formation. A UV-LED module emitting at 275 nm was demonstrated with the developed growth technology, and illuminated with an irradiation power of 2.6 mW cm −2 on SARS-CoV-2 samples. Over 99.999 % of viruses were inactivated within 5 s owing to the high power of this module.